Originally Posted by

**Status** - "Newton's Law of Cooling states that the rate of change of the temperature of an object is proportional to the difference between its own temperature and the temperature of its surroundings."

Going by the example I did in class:

$\displaystyle \text {Let T = temperature of the cake, and t = time.}$

$\displaystyle \frac{ dT}{dt } = k(T - 70) $

$\displaystyle \int \frac{dT}{T-70} = \int kdt$

$\displaystyle ln(T-70) = kt + C$

$\displaystyle T-70 = Ce^{kt}$ Mr F says: No! You have already used C in the previous line See below.

$\displaystyle T = Ce^{kt} + 70$

Am I on the right track?...